Spatial structure and community dynamics of arboreal ants in tropical rainforests - Mottl, Ondřej (Jihočeská univerzita, 2019)
This thesis explores the drivers of distribution patterns and community structure of ant communities in tropical rainforest. The aim is to test how diverse arboreal ant communities are shaped by ecological gradients such as latitude, succession or forest strata, on both small and large spatial scales. This work represents a compilation of studies based on observational patterns as well as field experiments. Plot-based sampling and advanced statistics (e.g. multivariate analyses, rarefactions, and null-models) are used throughout the thesis to explore ant distribution in tropical forests. Manipulative experiments with artificial nests, and inter- and intra-behavioural trials, are used to test the hypotheses of non-random vertical species distribution (community stratification) and segregation within- and across- individual trees (ant mosaics). The effect of secondary succession on canopy ants is disentangled using unique montane forest datasets and the results are compared with previous lowland-based studies. On large geographical scale, general patterns of ant abundances are described along a latitudinal gradient and used to test the hypothesis of spatial segregation of ants with other arthropods on individual trees. The thesis results suggest that the behaviour of individual species and microhabitats are more important factors at a local scale, while forest structure and climate influence ants over larger scales.
Spatial structure and community dynamics of arboreal ants in tropical rainforests